2010
DOI: 10.1002/wcs.52
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and cognition

Abstract: Sleep is a complex physiologic state, the importance of which has long been recognized. Lack of sleep is detrimental to humans and animals. Over the past decade, an important link between sleep and cognitive processing has been established. Sleep plays an important role in consolidation of different types of memory and contributes to insightful, inferential thinking. While the mechanism by which memories are processed in sleep remains unknown, several experimental models have been proposed. This article explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Sleep‐deprived individuals show deficits in executive function, attention and memory tasks. Such cognitive deficits in the setting of sleep deprivation have also been demonstrated in real‐life circumstances (Deak & Stickgold, ). Most sleep‐deprivation studies have focused on its impact on memory performance (Duclos et al., ; Walker & Stickgold, ).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Sleep‐deprived individuals show deficits in executive function, attention and memory tasks. Such cognitive deficits in the setting of sleep deprivation have also been demonstrated in real‐life circumstances (Deak & Stickgold, ). Most sleep‐deprivation studies have focused on its impact on memory performance (Duclos et al., ; Walker & Stickgold, ).…”
Section: Introductionmentioning
confidence: 81%
“…Over the past decade, an important link between sleep and cognitive processing has been established in both normal and abnormal populations (Chambers, ; Deak & Stickgold, ). Previous studies indicate that sleep promotes various cognitive functions, including decision‐making, language learning, categorization, executive functions and memory (Chambers, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown decreased sleep efficiency as well as more sleep disturbances and daytime sleepiness in adults with POTS [14, 15]. Decreased sleep time and sleep quality have been shown to impair performance on various cognitive tasks [16]. How sleep efficiency affects cognition in POTS patients is unknown but, we can postulate that sleep quality is a major contributor to brain fog in POTS.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep plays a pivotal role in learning and memory processes (2,3). Therefore, SD may affect the subsequent learning capacity and the ability to form new memories (3).…”
Section: Discussionmentioning
confidence: 99%